Efektivitas Model Pembelajaran Kooperatif Tipe TPS-TGT Pada Pembelajaran Matematika di Kelas VIII SMPN 1 Makassar - Andi Aras (IAIN PAREPARE, 2018)
This type of research is an experimental study which aims to describe theeffectiveness of the cooperative learning model TPS-TGT type in mathematicslearning in class VIII SMP N 1 Makassar. The sample in this study class VIII.5 wastaught by cooperative learning model TPS-TGT type taken using techniques clusterrandom sampling. The data collected consisted of data on student learningoutcomes, data on learners' motivation, data on student activities during thelearning process, and data on student responses to the application of cooperativelearning models of the TPS-TGT type.The results showed that the score of mathematics learning outcomes of students inclass VIII.5 was in the high category with a mean of 80.15 and a standarddeviation of 9.79, completeness in classics was 82.5%, the average normalizedgain was in the high category, scores the average learning motivation of students isin the high category, the average gain normalized learning motivation is in themedium category, the activity of students in following the learning process is in agood category, and student responses to the application of the cooperative learningmodel TPS-TGT type are positive. In general, it was concluded that the cooperativelearning model type TPS-TGT was effectively applied to mathematics learning in class VIII.5 of SMP N 1 Makassar. The results of the hypothesis test at a significant level α = 0.05 with the t-test show that H1 is accepted which means that the cooperative learning model type TPSTGTis effectively applied to mathematics learning in SPLDV material in class VIIIof SMP N 1 Makassar.